MAPEO DE TIPOLOGÍAS DE VEGETACIÓN DE CAATINGA A PARTIR DE IMÁGENES ORBITALES Y GEOBIA: ESTUDIO DE CASO DE LA CUENCA DEL RÍO TAPEROÁ, REGIÓN SEMIÁRIDA DE BRASIL - Sperle da Silva, Diego Vicente (2023)
The caatinga vegetation is an exclusively Brazilian biome located in the country's semiarid region, paradoxically being one of the less studied and mapped biomes. This vegetation is full of endemic species and has a great variety of landscapes, despite being under constant drought conditions. Due to the seasonal natural dynamics of the semiarid, where in dry periods the vegetation loses most of the leaves, mapping the caatinga vegetation from remote sensing images is challenging. In this work, two different dates of Landsat 8 images were used, one for the wet period and another for the dry period, to map different types of caatinga described by CAVALCANTI (2014). GEOBIA was used to model the knowledge of the chosen classes, based on known parameters of each class. A field work was made  to collect data and control points, and subsequent validation of the modeling and final mapping. An “almost perfect” Kappa index was obtained for all classes in the final map. These results show the potential of using the model used to map the caatinga vegetation in other areas.